Penilaian Kinerja Investasi TI Menggunakan Val IT 2.0 pada Aplikasi Kependudukan Online Pemerintah Kota X - Moch Aldoris Williandy; Mohammad Imamuddin Adani; Renny Sari Dewi (JURIKOM (Jurnal Riset Komputer), 2020)
The use of information technology (IT) now has experienced a very big change, from merely a tool to interact, now turning to the forefront in community service, especially in Government Institutions. Increasingly the issue of Smart City is encouraging every city in Indonesia to continue to innovate in developing information technology. The Val IT Framework provides guidelines, processes and practical support that can help leaders of government agencies understand and carry out their role as determinants of IT application development. Val IT consists of 3 (three) main process domains, namely Value Governance, Portfolio Management and Investment Management. This research is expected to be able to assess the development of information technology applications carried out at City Government Institution X as a case study place, so that the institution's management can determine the best decisions in developing its information technology.